Antiracist Praxis in Public Health: A Call for Ethical Reflections. Issue 2 (11th April 2021) - Fletcher, Faith E.; Jiang, Wendy; Best, Alicia L.
Abstract: The Covid‐19 pandemic has revealed myriad social, economic, and health inequities that disproportionately burden populations that have been made medically or socially vulnerable. Inspired by state and local governments that declared racism a public health crisis or emergency, the Anti‐Racism in Public Health Act of 2020 reflects a shifting paradigm in which racism is considered a social determinant of health. Indeed, health inequities fundamentally rooted in structural racism have been exacerbated by the Covid‐19 pandemic, which calls for the integration of antiracist praxis to promote ethical public health research processes. This commentary describes ways in which antiracist praxis—which emphasizes empowerment of traditionally marginalized populations—offers strategies to explicitly address power imbalance, stigmatization, and other consequences of structural racism in public health research .